2014
DOI: 10.1039/c4dt00198b
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear zinc(ii) complexes containing (benzimidazol-2-yl)benzene that overcome drug resistance in hepatocellular carcinoma cells through induction of mitochondria fragmentation

Abstract: Herein we demonstrated that dinuclear zinc complexes could overcome drug resistance in R-HepG2 drug resistance hepatocellular carcinoma cells through induction of mitochondria-mediated apoptosis or by triggering mitochondria fragmentation, depletion of the membrane potential and intracellular ATP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The loss of mitochondrial membrane potential is an indication that apoptosis proceeds by a mitochondrial pathway 28. Damage to mitochondria leads to its depolarization with a drop in Δ Ψ m 48,49. JC‐1 is a lipophilic cationic dye that spontaneously forms aggregates in healthy cells with high mitochondrial potential (Δ Ψ m ); this results in intense red fluorescence (ca.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of mitochondrial membrane potential is an indication that apoptosis proceeds by a mitochondrial pathway 28. Damage to mitochondria leads to its depolarization with a drop in Δ Ψ m 48,49. JC‐1 is a lipophilic cationic dye that spontaneously forms aggregates in healthy cells with high mitochondrial potential (Δ Ψ m ); this results in intense red fluorescence (ca.…”
Section: Resultsmentioning
confidence: 99%
“…A trimeric complex has been obtained through the self assembly of cyclometalated trinuclear palladium(II) complexes (Rü ttimann et al, 1993). Dinuclear zinc complexes containing (benzimidazol-2-yl)benzene based ligands have shown anticancer activities (Xie et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%
“…For instance, Terenzi et al found that zinc complexes based on 2,5-diphenyl [1,3,4]oxadiazole derivative could bind to DNA and inhibit the proliferation of human carcinoma cells. In recent, zinc complexes based on benzimidazole compound draw our attention for their biological activities [7][8]. Esophageal cancer has the highest incidence and mortality rates in China.…”
Section: Introductionmentioning
confidence: 99%